Effect of blockage ratio on backlayering length of thermal smoke flow in a longitudinally ventilated tunnel - Meng, Na; Liu, Xiaomei; Li, Xiao; Liu, Beibei (Applied thermal engineering, 2018)
•Experimental study on backlayering length of thermal smoke flow in a model tunnel.•Blockages with different blockage ratios upstream of fire source were considered.•The effect of blockage ratio on backlayering length was studied.•A new expression was proposed to predict the backlayering length. Experiments were conducted in a reduced-scale tunnel to investigate the effect of blockage ratio on backlayering length in a longitudinally ventilated tunnel. Model vehicle blockages are placed upstream of the fire source and blockage ratios are ranged in 0.13–0.51. It is found that when there is no blockage in the tunnel, experimental data can be well correlated by Li model. However, when there is blockage upstream of the fire source, the backlayering length is shown to be lower than the predictions of Li model. Tang model fails to collapse the experimental data in the present work due to the difference in blockage ratio. A new expression by considering the factor blockage ratio is proposed to predict the backlayering length of smoke flow, which is shown to well collapse the experimental measurements.